2009
DOI: 10.1002/adv.20153
|View full text |Cite
|
Sign up to set email alerts
|

Online control of the injection molding process based on process variables

Abstract: ABSTRACT:The conventional control of the injection molding process is based on machine variables, which cannot sufficiently characterize the course of the process. Hence, a system that controls the injection molding process based on process variables has been developed at the Institute of Plastics Processing at RWTH Aachen University during the last years. It controls the quality determining process variable cavity pressure directly and realizes a desired course of cavity pressure in the injection and holding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…2 Matching eqs 3 and 6, and rearranging, one obtains the relationship for local pressure profile (valid for t > t sol and Fo > 0.1).…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…2 Matching eqs 3 and 6, and rearranging, one obtains the relationship for local pressure profile (valid for t > t sol and Fo > 0.1).…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…Both control methods reduced variance in part weight. Michaeli et al (2004Michaeli et al ( , 2009) developed an online cavity pressure controller, which realized a constant gradient of the cavity pressure during the filling phase and calculated the cavity pressure with a PVT optimization in the holding pressure phase. They indicated that the specific volume displays a significant dependence on the viewed disturbance variables, in particular the melt/mold temperature.…”
Section: Development Of Process Control Methods With Polymer Pvt Propmentioning
confidence: 99%
“…The above studies used different types of sensors, mostly flat specimens in the same thickness for research, while seldom discussing the molded part in nonuniform thicknesses. The injection molding process often uses direct cavity pressure for real-time monitoring and control, as the cavity pressure has higher accuracy than the pressure in other positions, e.g., pressure of hydraulic line or injection nozzle [37]. Installing the cavity pressure/ temperature sensor in the cavity can obtain an accurate history profile; however, the molded product of the cavity will be faulty.…”
Section: Introductionmentioning
confidence: 99%